Determination of Plasma Osteopontin and Serum Inhibin B in Pregnant Women with Preeclampsia - Mehde, Atheer A; Mehdi, Wesen A; Mustafa, Seenaa A (Al-Nahrain Journal of Science, 2018)
Pre-eclampsia is a multisystem disorder of pregnancy, which complicates 3%-5% of pregnancies in the world .The present study deals with estimation of levels of Osteopontin, Inhibin B, protein, albumin, globulin and Alb./Glb. ratio in forty five Pregnant Women with Preeclampsia in comparison with thirty healthy Pregnant Women. In Pregnant Women with Preeclampsia, the level of Osteopontin and Inhibin B were significantly higher as compared to the normal subjects [p<0.01]. In Pregnant Women with Preeclampsia the levels of S. calcium S.Protein and albumin were significantly decreased as compared to the normal subjects [p<0.05, p<0.05and p<0.01] respectively. Based on findings of the present study, it can be concluded that Patients with Preeclampsia had significantly higher serum inhibin B and Osteopontin concentrations compared to healthy pregnant women. In addition, the current study could not determine any links between Osteopontin levels and other biochemical markers in this study.